2013
DOI: 10.1111/idj.12034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of antibiotics in the treatment of peri-implantitis

Abstract: The significance of adjunctive antibiotic therapy in the treatment of peri-implantitis remains debatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
(117 reference statements)
2
45
0
Order By: Relevance
“…105 Moreover, results from a systematic review reported that the significance of using antibiotics as adjuncts to conventional peri-implantitis therapies remains debatable. 23 Because there is heterogeneity of studies, which have used experimental combinations of different decontamination methods, it is exigent to establish a single standardized protocol for implant decontamination for the treatment of peri-implantitis. However, further information regarding implant surface decontamination is published elsewhere.…”
Section: Antibiotics In the Treatment Of Peri-implant Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Moreover, results from a systematic review reported that the significance of using antibiotics as adjuncts to conventional peri-implantitis therapies remains debatable. 23 Because there is heterogeneity of studies, which have used experimental combinations of different decontamination methods, it is exigent to establish a single standardized protocol for implant decontamination for the treatment of peri-implantitis. However, further information regarding implant surface decontamination is published elsewhere.…”
Section: Antibiotics In the Treatment Of Peri-implant Diseasesmentioning
confidence: 99%
“…These treatment strategies encompass use of antiseptics and/or antibiotics, laser therapy, guided bone regeneration, and photodynamic therapy. [16][17][18][19][20][21][22][23] The aim of this article was to review indexed literature with reference to the various therapeutic interventions proposed for the management of peri-implant diseases.…”
mentioning
confidence: 99%
“…Some studies [7,8] have reported that SRP when performed with adjunct antibiotic therapy is more effective in the treatment of periodontal disease than when SRP is done alone. However, results from a systematic review showed that the significance of antibiotic therapy as a potential adjunct to SRP is debatable [9]. To overcome the limitations of scaling and root planing and to reduce the bacterial load, antimicrobial photodynamic therapy (aPDT) has been proposed as a treatment strategy for AgP.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a certain therapeutic has been shown to reduce coronary heart disease and limit the inflammation treatment [17]. In addition, bacterial composition on the implant materials may cause of peri-implantitis, which will influence the success and survival rates of implant materials [18,19]. Therefore, antibacterial efficacy must be considered during medical devices' implantation.…”
Section: Introductionmentioning
confidence: 99%